Three Essays on the macroeconomic effects of liquidity cycles: an SFC growth models approach - GUILHERME LEONEL SINGH (2021)
This dissertation presents three essays that discuss the effects of the financial cycle, financial development, and financial integration on emerging market economies (EME) using stock-flow consistent (SFC) models. The first essay develops a stock-flow consistent growth model for a small open emerging market economy with an endogenous exchange rate. The main goal is to assess the consequences of exchange rate devaluation transmitted via sectoral balance-sheet to the economy. This essay advances with an endogenous exchange rate determination that encompasses the short-term foreign currency market and heterogeneous dealers operating on the currency market. This setting enables for the evaluation of the different shares of “chartists” dealers, and for the occurrence of the pass-through effect of the exchange rate to import prices. Experiments show a negative effect of a devaluation, regardless of the existence of a passthrough effect on the exchange or different composition of heterogenous dealers. Devaluations also might lead to the increase of the external vulnerability of the domestic economy because of the rise in gross external debt (currency mismatch) and increase the public debt maturity (maturity mismatch). The second essay discusses the occurrence of international liquidity cycles, the private sector’s engagement on external debt, and the emergence of new forms of external vulnerability in emerging market economies. The international liquidity cycles are examined in two experiments, emulating the boom and the bust phases. The work advances with the firms’ external debt allocation response to financial performance indicators. Also, private banks’ decision to issue bonds abroad is described considering different strategies for the balance-sheet management and depending on the phase of the cycle. Results suggest that private debt is interconnected and related to the new forms of external vulnerability. Firms’ funding decision affects banks’ balance-sheet, triggering different reactions. A conflicts relation between firms and banks is reported, with each sector taking advantage over the other depending on the phase of the cycle. The third essay explores accumulation and its relations with the liquidity cycle, distribution, and financial innovation. The goal is to reassess the hypothesis of the crowd-out of investment due to higher financial investment, profit distribution, and higher uncertainty. The model innovates by including financial assets as a part of the firm’s portfolio decision, also, by encompassing the leverage rate in the investment function to emulate Kalecki’s “increasing risk principle”. Results confirm a deleterious effect on accumulation due to the factor analyzed. Nonetheless, the causality seems to run from a higher leverage rate to lower investment via the increasing risk principle. Altogether, the dissertation advances with the post-Keynesian theory and with the SFC tradition of growth models. In particular, each model advances with the discussion about the transmission of the liquidity cycles on emerging open economies, and the respective macroeconomics consequences. Open economy issues, financial innovation, external vulnerability, and macroeconomic fragility consist of topics that populate this dissertation.